Diagnóstico de síndrome de Mayer-Rokitansky-Küster-Hauser - Berrios Pacheco, Luis Felipe (2026)
Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome is a rare congenitalmalformation characterized by agenesis or hypoplasia of the uterus and the upper third of the vagina, in patients with a forty-six, XX karyotype and normal secondary sexual development. We present the case of a 12-year-old female patient with primary amenorrhea and hypogastric pain. Imaging studies revealed hematometra secondary to distal vaginal obstruction. Magnetic resonance imaging and laparoscopy confirmed the presence of a functioning hypoplastic uterus, absence of the cervix,and a short vaginal canal, findings consistent with type I MRKH. Emergency surgical drainage was performed. Comprehensive management of this syndrome requires a multidisciplinary approach for diagnosis, surgical intervention, and psychologicalsupport, due to its reproductive, emotional, and social impact.